Pemberian Intervensi Pijat Refleksi Kaki Pada Lansia Dengan Hipertensi Yang Mengalami Masalah Gangguan Pola Tidur Di PPSLU Dewanata Cilacap - Wahyu Adi Arbianto; Prasanti Adriani (Jurnal Ventilator, 2023)
Introduction: Older adult with hypertension often experience several problems, one of which is disturbed sleep patterns. Disorders of sleep patterns experienced by the elderly have an impact on the recurrence of the disease, therefore the problem of sleep quality in the elderly must be addressed immediately One of them is providing foot massage reflexology Methods: This study uses a descriptive research design with a case study approach. This research is a study of the application of foot reflexology in the elderly with hypertension with nursing problems with sleep pattern disorders Result: The results of the study at the beginning of the study, on 3 Mey 2023 it was known that the respondent had problems with sleep patterns with a PSQI score of 18. Based on the evaluation results on 5 Mey 2023, it can be concluded that there was an increase in the quality of sleep of respondents with a PSQI score of 9 by giving intervention for 3 days starting from 3-5 Mey 2023 Discussion: Providing an effective foot massage reflexology intervention to overcome the problem of sleep pattern disorders in the elderly with hypertension, foot massage reflexology can relax the body so that sleep will feel more restful, foot massage reflexology intervention is recommended to be given every bedtime.